CONCEPT OF MULTI-LEVEL INTELLIGENT TECHNOLOGY FOR CONTROL OF GROUND MOBILE ROBOTIC PLATFORMS - NIKONOV, OLEH; FILIPOV, VIACHESLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The concept of building a multi-level intelligent technology for controlling ground mobile robotic platforms of special purpose is presented. The need to integrate multi-level control systems, sensor complexes, navigation algorithms and protection means into a single software and hardware environment is substantiated. The proposed concept is based on the hierarchical organization of levels of intelligent data processing: from the sensor level to the strategic mission control level. An analysis of modern approaches is carried out and the prospects for the practical application of multi-level technology in the creation of new generation robotic systems are determined. The results of the study indicate that the integration of multi-level intelligent technologies can significantly increase the autonomy and functional reliability of robotic systems. At the same time, the proposed approach not only meets modern challenges, but also lays the foundation for creating new generation platforms capable of adapting to unpredictable conditions and ensuring the performance of complex tasks with minimal operator involvement. The implementation of hybrid solutions is a key element of the concept of multi-level intelligent control technology for ground mobile robotic platforms, which allows combining hardware, software and organizational security measures, increases the survivability and fault tolerance of the platform, ensures adaptability to a changing environment and threats, and also contributes to the effective performance of tasks in difficult operating conditions. Thus, the proposed concept is the basis for the formation of a new paradigm in the design of ground robotic systems, and further scientific research will contribute to its practical implementation and improvement in the direction of creating high-tech solutions capable of meeting the challenges of the future.
Keywords: intelligent technologies; robotic platforms; multi-level architecture; sensor systems; software-hardware system; operator interface